Learning the lessons of life well to succeed - Abd Razak, Dzulkifli (2008)
BY now, most of the new students joining Malaysian universities must have settled down. Orientation would be over and the sooner one adjusts to the new lifestyle, the better. Much of what the students do will shape the image of the university and higher education. More often than not, this would translate into academic performance. While this is not entirely wrong, it is also not the best way to characterise a successful tertiary education. In other words, the university must be the place to discover and realise one's potentials and dreams. This should encompass not only the academic aspects but, equally important, the sociocultural dimensions. It is not good enough to remain just a bookworm or in a narrow confine of discipline without building up any interests in other interrelated fields.